Immunosuppressive environment in response to androgen deprivation treatment in prostate cancer - Qin, Caipeng; Wang, Jing; Du, Yiqing; Xu, Tao (Frontiers in Endocrinology, 2022)
Rationale: To invest the role of androgen deprivation therapy (ADT) on the tumor immune microenvironment of prostate cancer. Methods: Here we have profiled the transcriptomes of 19,227 single cells from 4 prostate tumors, including two cases who received ADT. To validated the single-cell analysis we use another group of patients receiving neoadjuvant ADT. Results: After receiving ADT treatment, the killing effect of prostate cancer immune cells on tumors is weakened, the interaction between immune cells and tumor cells is weakened, and the proportion of immunosuppressive cells Myeloid-derived suppressor cell (MDSC) and Regulatory T cells (Treg) cells increases. Conclusions: Our results highlight that ADT induces immunosuppressive in the prostate tumor microenvironment. These data have important implications for combining ADT with immunotherapy.